Relationship of compensation and productivity in Indonesia - Saefudin Zuhri; Dasih Irma; Nendi Juhandi (Privietlab, 2022)
This study aim to knowing level productivity employee, for analyze connection compensation to productivity employees. Based on results research, then expected could give benefit as following, could knowing to use compensation for employee, become something reference for study future, could knowing the resulting relationship Among compensation and productivity employee, could knowing type compensation like what is needed employee, could knowing origin origin compensation provided by the company. The population we will use for study this are employees work company. This study will take sample towards employees work with share questionnaire to 60 employees. In research this time, we will test is to connection among compensation and productivity employees and how much strong connection. Based on results study as well as data analysis can concluded that there is significant relationship among Compensation and Productivity Employee with nature connection Strong and Unidirectional.